Typology of Learning The Meaning of Hadith on Yusuf Al-Qaradhawiy Perspective - Eli Sabrifha; Khairunnas Jamal; Mochammad Novendri S (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2022)
This article is entitled typology of learning the meaning of hadith according to Yusuf Al-Qardhawi in his book entitled Kaifa Nata'amal Ma al-Sunnah Al-Nabawiyah. In understanding a hadith text, al-Qardhawi also often uses several approaches in explaining the meaning of sentences both in text and context. This article examines how al-Qardhawi applies methods to differences in understanding hadith, and how al-Qardhawi's method resolves dualism of opinion in one hadith text and meaning in its interpretation. Using a descriptive-analytical approach, this article examines the basic concepts of different ways of understanding hadith, looks for the roots of the character's thoughts, explains the advantages and disadvantages of the method including its implications. From the results of the discussion, it can be concluded that the patterns used include studying the meaning of hadith according to the instructions of the Qur'an, analyzing the opposite of a hadith with the Qur'an, collecting hadith in one theme, merging and interpreting hadith, understanding hadith historically, paying attention to the meaning of haqiqi and majazi and ascertaining the meaning and connotation of words in the hadith.